Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Sure, let's solve for [tex]\( x \)[/tex] and [tex]\( y \)[/tex] step-by-step given the matrices [tex]\( A \)[/tex], [tex]\( B \)[/tex], and [tex]\( C \)[/tex], and the resulting matrix [tex]\((A + B) - C\)[/tex].
Given:
[tex]\[ A = \left[\begin{array}{cc} 4 & 5 \\ 8 & 7 \\ x & y \end{array}\right], \quad B = \left[\begin{array}{cc} 0 & 2 \\ 2 & 3 \\ 4 & 5 \end{array}\right], \quad C = \left[\begin{array}{cc} -1 & 2 \\ 3 & -4 \\ 0 & 1 \end{array}\right] \][/tex]
And the result is:
[tex]\[ (A + B) - C = \left[\begin{array}{cc} 5 & 4 \\ 7 & 14 \\ 7 & 6 \end{array}\right] \][/tex]
### Step 1: Calculate [tex]\( A + B \)[/tex]
Let's add matrices [tex]\( A \)[/tex] and [tex]\( B \)[/tex]:
[tex]\[ A + B = \left[\begin{array}{cc} 4 + 0 & 5 + 2 \\ 8 + 2 & 7 + 3 \\ x + 4 & y + 5 \end{array}\right] = \left[\begin{array}{cc} 4 & 7 \\ 10 & 10 \\ x + 4 & y + 5 \end{array}\right] \][/tex]
### Step 2: Calculate [tex]\( (A + B) - C \)[/tex]
Now, let's subtract matrix [tex]\( C \)[/tex] from [tex]\( A + B \)[/tex]:
[tex]\[ (A + B) - C = \left[\begin{array}{cc} 4 & 7 \\ 10 & 10 \\ x + 4 & y + 5 \end{array}\right] - \left[\begin{array}{cc} -1 & 2 \\ 3 & -4 \\ 0 & 1 \end{array}\right] \][/tex]
[tex]\[ (A + B) - C = \left[\begin{array}{cc} 4 - (-1) & 7 - 2 \\ 10 - 3 & 10 - (-4) \\ (x + 4) - 0 & (y + 5) - 1 \end{array}\right] = \left[\begin{array}{cc} 5 & 5 \\ 7 & 14 \\ x + 4 & y + 4 \end{array}\right] \][/tex]
### Step 3: Set up equations and solve for [tex]\( x \)[/tex] and [tex]\( y \)[/tex]
We know that:
[tex]\[ (A + B) - C = \left[\begin{array}{cc} 5 & 4 \\ 7 & 14 \\ 7 & 6 \end{array}\right] \][/tex]
By comparing the third row:
[tex]\[ [x + 4, y + 4] = [7, 6] \][/tex]
This gives us two equations:
1. [tex]\( x + 4 = 7 \)[/tex]
2. [tex]\( y + 4 = 6 \)[/tex]
Solving these equations:
1. [tex]\( x + 4 = 7 \)[/tex]
[tex]\[ x = 7 - 4 \][/tex]
[tex]\[ x = 3 \][/tex]
2. [tex]\( y + 4 = 6 \)[/tex]
[tex]\[ y = 6 - 4 \][/tex]
[tex]\[ y = 2 \][/tex]
Thus, the values for [tex]\( x \)[/tex] and [tex]\( y \)[/tex] are:
[tex]\[ x = 3 \][/tex]
[tex]\[ y = 2 \][/tex]
Given:
[tex]\[ A = \left[\begin{array}{cc} 4 & 5 \\ 8 & 7 \\ x & y \end{array}\right], \quad B = \left[\begin{array}{cc} 0 & 2 \\ 2 & 3 \\ 4 & 5 \end{array}\right], \quad C = \left[\begin{array}{cc} -1 & 2 \\ 3 & -4 \\ 0 & 1 \end{array}\right] \][/tex]
And the result is:
[tex]\[ (A + B) - C = \left[\begin{array}{cc} 5 & 4 \\ 7 & 14 \\ 7 & 6 \end{array}\right] \][/tex]
### Step 1: Calculate [tex]\( A + B \)[/tex]
Let's add matrices [tex]\( A \)[/tex] and [tex]\( B \)[/tex]:
[tex]\[ A + B = \left[\begin{array}{cc} 4 + 0 & 5 + 2 \\ 8 + 2 & 7 + 3 \\ x + 4 & y + 5 \end{array}\right] = \left[\begin{array}{cc} 4 & 7 \\ 10 & 10 \\ x + 4 & y + 5 \end{array}\right] \][/tex]
### Step 2: Calculate [tex]\( (A + B) - C \)[/tex]
Now, let's subtract matrix [tex]\( C \)[/tex] from [tex]\( A + B \)[/tex]:
[tex]\[ (A + B) - C = \left[\begin{array}{cc} 4 & 7 \\ 10 & 10 \\ x + 4 & y + 5 \end{array}\right] - \left[\begin{array}{cc} -1 & 2 \\ 3 & -4 \\ 0 & 1 \end{array}\right] \][/tex]
[tex]\[ (A + B) - C = \left[\begin{array}{cc} 4 - (-1) & 7 - 2 \\ 10 - 3 & 10 - (-4) \\ (x + 4) - 0 & (y + 5) - 1 \end{array}\right] = \left[\begin{array}{cc} 5 & 5 \\ 7 & 14 \\ x + 4 & y + 4 \end{array}\right] \][/tex]
### Step 3: Set up equations and solve for [tex]\( x \)[/tex] and [tex]\( y \)[/tex]
We know that:
[tex]\[ (A + B) - C = \left[\begin{array}{cc} 5 & 4 \\ 7 & 14 \\ 7 & 6 \end{array}\right] \][/tex]
By comparing the third row:
[tex]\[ [x + 4, y + 4] = [7, 6] \][/tex]
This gives us two equations:
1. [tex]\( x + 4 = 7 \)[/tex]
2. [tex]\( y + 4 = 6 \)[/tex]
Solving these equations:
1. [tex]\( x + 4 = 7 \)[/tex]
[tex]\[ x = 7 - 4 \][/tex]
[tex]\[ x = 3 \][/tex]
2. [tex]\( y + 4 = 6 \)[/tex]
[tex]\[ y = 6 - 4 \][/tex]
[tex]\[ y = 2 \][/tex]
Thus, the values for [tex]\( x \)[/tex] and [tex]\( y \)[/tex] are:
[tex]\[ x = 3 \][/tex]
[tex]\[ y = 2 \][/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.